The Effect of Product Quality, Suitability, Promotion, and Religiosity as Moderating Variables on Public Interest in Using Sharia Life Insurance in South Jakarta. - Muhammad Hafizh Rizqi; R. Melda Maesarach (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study examines the influence of product quality, suitability, and promotion on public interest in using Sharia life insurance in South Jakarta, with religiosity as a moderating variable. Employing a quantitative approach, data were collected from 104 respondents through an online questionnaire and analyzed using Structural Equation Modelling-Partial Least Squares (SEM-PLS). the results indicate that promotion is the most dominant factor influencing public interest and religiosity, emphasizing the need for effective promotional strategies. Product quality and suitability also positively impact public interest, while religiosity does not significantly moderate these relationships. Instead, religiosity plays an indirect and contextual role, depending on its interaction with other variables. The validity and reliability tests confirm the robustness of the measurement model, ensuring the credibility of findings. However, the insignificant effect of religiosity on public interest suggests the need for further exploration of its moderating role. This study highlights the crucial role of promotion in driving public interest, while religiosity requires deeper examination in future research.